Effect of Banana Bark and Cow's Blood Meal Compost on the Green Lettuce Plants (Lactuca sativa L.) Growth - Pratiwi, Ambar; Wulandari, Ayu (Journal of Biotechnology and Natural Science, 2023)
Green lettuce (Lactuca sativa L.) is a vegetable crop that is in great demand by the public, but its production is relatively low so that it cannot meet the high market demand. One of the efforts to increase the production of green lettuce plants is by applying organic fertilizer. The purpose of this study was to determine the content of C, N, P, K elements, the effect of compost application for growth and optimal dosage. The research method used a complete randomized design (CRD) four treatments namely Control, A (dose of 60 g), B (dose of 120 g) and C (dose of 180 g) with 5 replications. Data from the study were analyzed using the Anova test, significant data continued with the DMRT 5% further test. Testing the effect with simple liner regression analysis. The results showed that compost gave a blackish brown color after 35 days and had no odor and obtained nutrient values of C (41,77%), N (6,92%), P (0,09%) and K (0,12%). The treatment of compost variations produced plant height of 26,80 cm, number of leaves of 10,60 leaf, plant wet weight of 22,40 gram, root weight of 0,57 gram, root length of 12,94 cm leaf area of 130,06 cm² with significant results, while chlorophyll A (0,19 mg/L) and total (0,616 mg/L) levels had insignificant results. The conclusion of the research is that the compost of banana stalks and cow blood meal contains C by 41,77%, Total N by 6,92%, Total P by 0,09% and Total K by 0,12%. Banana pith compost and cow blood flour had a significant effect on all parameters of green lettuce plant growth except leaf chlorophyll content at the most optimal dose was treatment A (dose of 60 g).